2005
DOI: 10.1158/0008-5472.can-05-0233
|View full text |Cite
|
Sign up to set email alerts
|

Seliciclib (CYC202, R-Roscovitine) Induces Cell Death in Multiple Myeloma Cells by Inhibition of RNA Polymerase II–Dependent Transcription and Down-regulation of Mcl-1

Abstract: Seliciclib (CYC202, R-roscovitine) is a cyclin-dependent kinase (CDK) inhibitor that competes for the ATP binding site on the kinase. It has greatest activity against CDK2/cyclin E, CDK7/ cyclin H, and CDK9/cyclin T. Seliciclib induces apoptosis from all phases of the cell cycle in tumor cell lines, reduces tumor growth in xenografts in nude mice and is currently in phase II clinical trials. This study investigated the mechanism of cell death in multiple myeloma cells treated with seliciclib. In myeloma cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
246
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(270 citation statements)
references
References 54 publications
22
246
0
2
Order By: Relevance
“…The molecular mechanism by which R-roscovitine achieves these promising results has not yet been elucidated. R-roscovitine is known to promote apoptosis in cancer cell lines by inhibition of RNA polymerase-II leading to down-regulation of the key survival protein Mcl-1 [24]. It has also been suggested that NF-kB activation at the level of IkB kinase kinase activity is inhibited by R-roscovitine [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism by which R-roscovitine achieves these promising results has not yet been elucidated. R-roscovitine is known to promote apoptosis in cancer cell lines by inhibition of RNA polymerase-II leading to down-regulation of the key survival protein Mcl-1 [24]. It has also been suggested that NF-kB activation at the level of IkB kinase kinase activity is inhibited by R-roscovitine [25].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, R-roscovitine is capable of overcoming survival signals such as GM-CSF to promote neutrophil apoptosis in vitro and resolution of inflammation in established animal models. R-roscovitine has been investigated previously from an anticancer perspective and has been found to promote apoptosis in myeloma cell-lines by down-regulation of Mcl-1 [24]; indeed R-roscovitine and other CDK inhibitors are undergoing Phase I and II clinical trials for the treatment of various types of cancers. Recently, it was shown that R-roscovitine could directly inhibit NF-kB at late time-points in cancer cell-lines [25], a finding that, if applicable to neutrophils, might provide insight into the antiinflammatory properties of R-roscovitine.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction is likely indirectly due to inhibition of CDK7/CDK9 complexes, whose activities are required for transcription of a variety of mRNAs including cyclin B1 and anti-apoptotic genes (MacCallum et al, 2005). We then tested the role of cyclin B1 and cyclin E1 directly by blocking the expression by RNAi.…”
Section: Discussionmentioning
confidence: 99%
“…For example, roscovitine may enhance the activity of CPT derivatives in vivo (Abal et al, 2004), via its effects on transcription in addition to its effects upon CDK1 and CDK2 (MacCallum et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation